2012
DOI: 10.1152/ajprenal.00165.2012
|View full text |Cite
|
Sign up to set email alerts
|

A urine-concentrating defect in 11β-hydroxysteroid dehydrogenase type 2 null mice

Abstract: In aldosterone target tissues, 11␤-hydroxysteroid dehydrogenase type 2 (11␤HSD2) is coexpressed with mineralocorticoid receptors (MR) and protects the receptor from activation by glucocorticoids. Null mutations in the encoding gene, HSD11B2, cause apparent mineralocorticoid excess, in which hypertension is thought to reflect volume expansion secondary to sodium retention. Hsd11b2 Ϫ/Ϫ mice are indeed hypertensive, but impaired natriuretic capacity is associated with significant volume contraction, suggestive of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In aldosterone target tissues, 11βHSD2 is coexpressed with mineralocorticoid receptors and protects the receptor from activation by glucocorticoids. It was found that decreased HSD11B2 activity is related to hypertension [ 21 ] and Hsd11b2 null mice are also hypertensive [ 22 ]. So, the increased Hsd11b2 transcription in ISIAH renal cortex may lead to decreased glucocorticoid action and be protective against excessive elevation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In aldosterone target tissues, 11βHSD2 is coexpressed with mineralocorticoid receptors and protects the receptor from activation by glucocorticoids. It was found that decreased HSD11B2 activity is related to hypertension [ 21 ] and Hsd11b2 null mice are also hypertensive [ 22 ]. So, the increased Hsd11b2 transcription in ISIAH renal cortex may lead to decreased glucocorticoid action and be protective against excessive elevation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The acute PN response has not been measured in Hsd11b2 ‐null mice but a chronic natriuresis develops as the disease progresses (Evans et al . ). This increased sodium excretion contracts ECFV but does not normalize BP and our data indicate that activation of the sympathetic nervous system may contribute both to the origins and maintenance of hypertension (Bailey et al .…”
Section: Time Line Of the Development Of Major Antihypertensive Theramentioning
confidence: 97%
“…A compelling argument for a causative role of the biochemical abnormalities is the observed complete reversibility of the sNDI with normalization of biochemistries after appropriate treatment. In this context, it is interesting to note the recent report of a urinary concentrating defect also in the mouse model of AME (Hsd11b2 Ϫ/Ϫ mice), which was indeed associated with a deficiency in Aqp2 mRNA (21). Curiously, the obvious experiment of confirming the reversibility of the urinary concentrating defect was not performed, despite the published clinical experience in humans.…”
Section: Implications For Mechanismsmentioning
confidence: 99%